PENERAPAN PENGELOLAAN SAMPAH BERBASIS MASYARAKAT (CBSWM) DI KOTA MANADO SEBAGAI PEMENUHAN HAK ATAS LINGKUNGAN HIDUP YANG BAIK DAN SEHAT - Yoan Barbara Runtunuwu (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2021)
The purpose of this study is an action to study and analyze the problems of waste management in residential areas and residential waste management and community-based waste management. In this study, we use a study based on literature study which is a legal norm, where the secondary materials obtained through library research are only library materials and legal secondary materials. The essence of this discussion is the implementation of integrated waste management in Manado City based on the provisions regarding waste. It is clearly stated that waste management is not only the responsibility of the government. As a waste producer, the community has to maintain cleanliness and environmental health. In this case, an administrative disposition must be applied to continue any problems found. As mentioned in this field, compliance is low and can provide a deterrent effect for those who are not aware of the importance of waste management.